PENGARUH PEMAHAMAN WRITING MATHEMATICS MAHASISWA DALAM MENGKOMUNIKASIKAN SUATU BUKTI PERNYATAAN DALAM MATEMATIKA - Nisfulaila, Intan (Universitas Insan Budi Utomo, 2021)
The ability to write and communicate Mathematical texts is needed to get a complete of understanding of a material in Mathematics. The ability to write good and correct Mathematics texts can be used as an indication that the writer is not only memorizing but also understanding what is being written and can be used as a measure that the writer understands the storyline that is conveyed to the reader. However, there are still many meaningless sentences and inappropriate use of Mathematical symbols. This can lead to misconceptions and the assumption that what is conveyed is correct according to the rules. In this study, data analysis was carried out qualitatively to review how much change in writing mathematics skills has occurred after a group of students received technical guidance. The results of data analysis and evaluation show that the ability to understand the rules of writing mathematics has an effects in communicating or creating proof of mathematical statements, although qualitatively the changes are not too significant.